2022
DOI: 10.1101/2022.09.09.22279694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct and joint effects of low and high levels of Aβ and tau deposition on cortical thickness

Abstract: Alzheimer's disease (AD) is defined by the presence of Amyloid-β (Aβ), tau, and neurodegeneration (ATN framework) in the human cerebral cortex. Prior studies have suggested that Aβ deposition can be associated with both cortical thinning and thickening. These contradictory results may be due to small sample sizes, the presence versus absence of tau, and limited detectability in the earliest phase of protein deposition, which may begin in young adulthood and cannot be captured in studies enrolling only older su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…This ambiguity is reflected in conflicting reports regarding the relationship between the two best biomarkers in our study: Aβ and ATH. Some studies suggest that an increase in Aβ deposition is linked with neurodegeneration, such as cortical thinning and/or lower volume (Becker et al, 2009;Glodzik et al, 2012;Doré et al, 2013;Kaffashian et al, 2015;Llado-Saz et al, 2015;Susanto et al, 2015;Hedden et al, 2016;Sala-Llonch et al, 2017;Ten Kate et al, 2018), while others report the opposite, where higher Aβ deposition is associated with cortical thickening and/or increased volume (Whitwell et al, 2013;Rahayel et al, 2019;Batzu et al, 2020;Harrison et al, 2021;Hojjati et al, 2023). Fortea et al (2011) examined the association between Aβ values and cortical thickness 2013) investigated non-Aβ factors of neurodegeneration within AD regions in older HC adults and found that many had neurodegenerative biomarker abnormalities in AD-affected brain regions, despite having normal Aβ levels.…”
Section: Discussionmentioning
confidence: 99%
“…This ambiguity is reflected in conflicting reports regarding the relationship between the two best biomarkers in our study: Aβ and ATH. Some studies suggest that an increase in Aβ deposition is linked with neurodegeneration, such as cortical thinning and/or lower volume (Becker et al, 2009;Glodzik et al, 2012;Doré et al, 2013;Kaffashian et al, 2015;Llado-Saz et al, 2015;Susanto et al, 2015;Hedden et al, 2016;Sala-Llonch et al, 2017;Ten Kate et al, 2018), while others report the opposite, where higher Aβ deposition is associated with cortical thickening and/or increased volume (Whitwell et al, 2013;Rahayel et al, 2019;Batzu et al, 2020;Harrison et al, 2021;Hojjati et al, 2023). Fortea et al (2011) examined the association between Aβ values and cortical thickness 2013) investigated non-Aβ factors of neurodegeneration within AD regions in older HC adults and found that many had neurodegenerative biomarker abnormalities in AD-affected brain regions, despite having normal Aβ levels.…”
Section: Discussionmentioning
confidence: 99%